Increased Microbial Butanol Tolerance by Exogenous Membrane Insertion Molecules. Issue 21 (25th September 2015) - Hinks, Jamie; Wang, Yaofeng; Matysik, Artur; Kraut, Rachel; Kjelleberg, Staffan; Mu, Yuguang; Bazan, Guillermo C.; Wuertz, Stefan; Seviour, Thomas
Abstract: Butanol is an ideal biofuel, although poor titers lead to high recovery costs by distillation. Fluidization of microbial membranes by butanol is one of the major factors limiting titers in butanol‐producing bioprocesses. Starting with the hypothesis that certain membrane insertion molecules would stabilize the lipid bilayer in the presence of butanol, we applied a combination of in vivo and in vitro techniques within an in silico framework to describe a new approach to achieve solvent tolerance in bacteria. Single‐molecule tracking of a model supported bilayer showed that COE1‐5C, a five‐ringed oligo‐polyphenylenevinylene conjugated oligoelectrolyte (COE), reduced the diffusion rate of phospholipids in a microbially derived lipid bilayer to a greater extent than three‐ringed and four‐ringed COEs. Furthermore, COE1‐5C treatment increased the specific growth rate of E. coli K12 relative to a control at inhibitory butanol concentrations. Consequently, to confer butanol tolerance to microbes by exogenous means is complementary to genetic modification of strains in industrial bioprocesses, extends the physiological range of microbes to match favorable bioprocess conditions, and is amenable with complex and undefined microbial consortia for biobutanol production. Molecular dynamics simulations indicated that the π‐conjugated aromatic backbone of COE1‐5C likely acts as a hydrophobic tether for glycerophospholipid acyl chains by enhancing bilayer integrity in the presence of high butanol concentrations, which thereby counters membrane fluidization. COE1‐5C‐mitigated E. coli K12 membrane depolarization by butanol is consistent with the hypothesis that improved growth rates in the presence of butanol are a consequence of improved bilayer stability. Abstract : Insane in the membrane : One strategy to make biobutanol more attractive economically is to boost production titers in bioprocesses. Herein, we describe a chemical intervention technique that instantly imparts butanol tolerance to microbes through desirable structural changes to their membranes. This is an important first step in increasing production titers in butanol‐producing bioprocesses and a significant conceptual departure from current strain‐improvement strategies.